Perbandingan Kinerja Model ARIMA pada Forecasting Harga Saham PT Erajaya Swasembada Tbk menggunakan Data Historis 10 Tahun, 5 Tahun dan 3 Tahun - Ribkah Duma Lalang; Kevin G. Djabibi; Raymond Axel Mara; Putri Widarajati; Radian Januari Situmeang (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to compare the performance of the Autoregressive Integrated Moving Average (ARIMA) model in forecasting the stock price of PT Erajaya Swasembada Tbk using 10-year, 5-year, and 3-year historical daily data. The research data consisted of daily stock prices from 2016–2025 obtained from Yahoo Finance and company fundamental data including revenue, net income, total assets, EPS, and ROE. The study employed a quantitative approach using time series forecasting analysis with the ARIMA model. The analysis stages included data preprocessing, stationarity testing using the Augmented Dickey-Fuller (ADF) Test, differencing, model identification through ACF and PACF plots, model selection based on Akaike Information Criterion (AIC), residual testing using the Ljung-Box Test, and accuracy evaluation using RMSE, MAE, and MAPE. The results showed that all data became stationary after first-order differencing. The best models obtained were ARIMA(0,1,0) for 10-year data, ARIMA(0,1,1) for 5-year data, and ARIMA(0,1,2) for 3-year data. Based on the evaluation results, the ARIMA(0,1,1) model using 5-year historical data produced the best forecasting performance with an AIC value of 9523.612 and a MAPE value of 1.826%. The forecasting results indicated that the stock price of PT Erajaya Swasembada Tbk is predicted to move relatively stable around IDR 407 per share for the next 20 trading days. This study indicates that the use of historical periods that are more relevant to current market conditions can produce more accurate forecasting results.